Three-dimensional printing elements for conformal cooling - Loh, Nicholas Weng Siong (Nanyang Technological University, 2023)
Conformal Cooling Channels has revolutionized the manufacturing industry’s outlook on its mold and die design, allowing for better thermal uniformity across its cooling stage, leading to faster process cyclic time. From the recent advances of three-dimensional (3D) printing technology, they provide new benefits and options for the industry to further improve its efficiency and productivity of the processes, in this case creating conformal cooling channels with complex internal geometries for enhanced thermal efficiency. This study shall investigate the thermal performance of 3D printed metallic lattice structures within the conformal cooling channels and its effect on its properties such as thermal conductivity, temperature uniformity and pressure drop. The experiment is conducted by comparing various lattice designs and its impact on its properties using an experimental setup, with analysis using computational fluid dynamic simulations being performed simultaneously. The results will then be evaluated based on the difference in said properties in determining the impact of said lattice structures in the production and design on conformal cooling channels. This study shall also be discussing the additive manufacturing techniques used in producing the test specimen, such as Selective Laser Melting and Direct Metal Laser Sintering. A comparison of the simulation results of all lattice-integrated channel designs showed the Face Centered Cubic lattice-integrated Tapered conformal channel design having the highest potential by achieving a balance of low temperature non-uniformity and pressure drop across the conformal cooling channel, with the circular hollow conformal channel design achieving the opposite. The lattice-integrated channel designs may be enhanced via additional experimentation of its operating parameters, as well as optimization of channel and lattice design for higher surface area for heat transfer and smaller impingement of coolant flow.